The Location Preferences for High-Rise Residential Among Young House Buyers in Johor Bahru - Normiesyahida Arissa Asrar; Noryanto Asroun Mohamad Asroun; Mohd Fadzli Mustaffa (Research in Management of Technology and Business, 2024)
Malaysia as a developing country faced rapid urban growth year by year. This situation has contributed to property price escalation in major cities including residential property prices. Out of 25,816 residential overhang units in 2023, 60.5 percent are from high-rise residential like condominium/apartment units. The intersection between location preferences and affordability becomes a pivotal aspect in shaping sustainable and inclusive housing solutions. The purpose of this study is to determine the most preferred high-rise residential location in Johor Bahru District among young house buyers. A questionnaire survey was used to collect data from a sample of 230 young house buyers. The data was analyzed using frequency analysis and mean score analysis. The study found that most of the respondents agreed that the most preferred location of high-rise residential should located near the workplace. This study could inform future urban development initiatives, promoting a more responsive and inclusive approach to city planning in response to contemporary social trends.